Peran Satuan Lalu Lintas Melalui Dikmas Lantas Dalam Menurunkan Angka Kecelakaan Lalu Lintas Di Wilayah Hukum Polres Kuningan - Jessica Debora Panjaitan (Indonesian Journal of Police Studies, 2017)
Traffic accidents in Kuningan area within the last 3 years. One of the traffic accidents is caused by the lack of knowledge and understanding of the rules and ethics in driving properly. Efforts made to reduce the number of traffic accidents are focused on pre-emptive efforts. A study was conducted to determine the description of traffic accidents, the role of Dikmaslantas, and the factors that affect Dikmaslantas. Discussed by using the concept and theory as a knife of analysis, namely using the concept of Dikmaslantas, the concept of Traffic Accidents, management theory, and communication theory. This research was conducted with a qualitative approach, using field research methods, as well as data collection techniques by interviewing, observing, and studying documents that have high traffic accident rates. The role of Dikmaslantas by Unitdikyasa in reducing the number of traffic accidents analyzed using management theory is to become a ceremonial coach, carrying out counseling, safety riding, and appeal activities that are still not optimal due to the high number of traffic accidents. The ability of Unitdikyasa personnel in terms of communication theory is still not optimal. Influencing factors, inhibiting factors are human resources, time and place, student attention and support, regulations on the Dikmaslantas, while supporting factors are cross-sectoral cooperation. Efforts have been made to reduce the number of traffic accidents. The author recommends increasing the number of personnel and providing vocational education (Dikjur), adding Sarpras, the need for innovations in Dikmaslantas activities to encourage public compliance with applicable traffic regulations.